2007
DOI: 10.1590/s0102-33062007000100001
|View full text |Cite
|
Sign up to set email alerts
|

Plant succession in a forest on the Lower Northeast Slope of Serra Geral, Rio Grande do Sul, and Holocene palaeoenvironments, Southern Brazil

Abstract: The study of plant succession provides information on vegetation dynamics of a region and, therefore, improves our understanding of the natural trends of present ecosystems. With this objective, plant succession based on palynology of a sediment profile in a swamp forest was studied on the Lower Northeast Slope of Serra Geral, Rio Grande do Sul. Samples were treated with HCl, HF, KOH and acetolysis; slides were mounted in glycerol-jelly. For each sample a minimum of 500 grains of pollen + pteridophyte and bryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 9 publications
1
17
0
4
Order By: Relevance
“…A pollen profile from São Francisco de Paula, on the eastern plateau of southernmost Brazil (Serra Geral), indicates that temperature and moisture increased at the beginning of the Holocene (Leonhardt and Lorscheitter 2010). The pollen record from Serra Velha on the lower slope of the Serra Geral about 330 km south of the Ciama 2 site shows the occurrence of Atlantic rainforest taxa at about 8800 and 5000 B.P., indicating the migration of tropical species from east to west since the early Holocene (Leal and Lorscheitter 2007). However, Behling (1995) demonstrated for the highlands of Santa Catarina state that Campos vegetation continued to prevail until ca.…”
Section: Holocene Vegetation Dynamicsmentioning
confidence: 97%
See 1 more Smart Citation
“…A pollen profile from São Francisco de Paula, on the eastern plateau of southernmost Brazil (Serra Geral), indicates that temperature and moisture increased at the beginning of the Holocene (Leonhardt and Lorscheitter 2010). The pollen record from Serra Velha on the lower slope of the Serra Geral about 330 km south of the Ciama 2 site shows the occurrence of Atlantic rainforest taxa at about 8800 and 5000 B.P., indicating the migration of tropical species from east to west since the early Holocene (Leal and Lorscheitter 2007). However, Behling (1995) demonstrated for the highlands of Santa Catarina state that Campos vegetation continued to prevail until ca.…”
Section: Holocene Vegetation Dynamicsmentioning
confidence: 97%
“…along the coastal plain and valleys of Rio Grande do Sul. More recently, Leal and Lorscheitter (2007) propose the occurrence of some Atlantic rainforest species in Serra Velha on the lower slopes of the Serra Geral, Rio Grande do Sul since 8800 B.P. However, with the exception of Behling et al (2004), who reported environmental changes over a time frame of 42840 B.P.…”
Section: Introductionmentioning
confidence: 99%
“…Para o sul do Brasil, nas últimas décadas, estes regimes climáticos têm sido discutidos em diversos trabalhos de palinologia do Quaternário, tais como: Behling (1993Behling ( , 1995Behling ( , 1998Behling ( , 2002; Neves (1991Neves ( , 1998; Neves & Lorscheitter (1992, 1995a, 1995b; Behling et al ( , 2004Behling et al ( , 2007; De Oliveira et al (2005); Leal & Lorscheitter (2007) e Macedo et al (2010), dentre outros.…”
Section: Introductionunclassified
“…Para o sul do Brasil, os regimes climáticos do Quaterná-rio têm sido discutidos em diversos trabalhos de palinologia: Behling (1993Behling ( , 1995Behling ( , 1998Behling ( , 2002; Neves (1991Neves ( , 1998; Neves & Lorscheitter (1992, 1995a, 1995b, 1996; Behling et al ( , 2004Behling et al ( , 2007; De Oliveira et al (2005); Leal & Lorscheitter (2007) e Macedo et al (2010).…”
Section: Introductionunclassified